شبكة النقل البري واثرها على النشاط السياحي في محافظة النجف الاشرف - اسعد سعيد لهمود (مجلة الغري للعلوم الاقتصادية والادارية)
المستلخص: یعد النقل أحد الأسباب المهمة لازدهار السیاحة في أي بلد، وبواسطة الطرق ووسائل النقل بأنواعها كافة یتم توفیر متطلبات أنشطة السیاحة والترویج في المكان المقصود، وكذلك یتم ربط الم ا زر السیاحي بأسواق الطلب، بما یعني أن النقل یمثل القاعدة الرئیسیة للسیاحة ورواجها، ویعبر أیضاً عن درجة التمدن والحضارة ومؤشر على مدى الرقي الاقتصادي للبلد. إن ازدهار صناعة السیاحة والترویح في أقالیم ودول العالم المختلفة یرتبط بتقدم طرق ووسائل النقل، ولا یمكن للمواقع السیاحیة أن تكون أكثر جذباً للسیاح طالما لا تتوفر لها إمكانیة الوصول بغض النظر عما تقدمه من تسهیلات وخدمات، وتؤثر وسائل النقل السریعة والمریحة على السیاحة والترویح فالمسافة والزمن مرتبطان، وسرعة وسائل النقل حالیاً جعلت العالم أشبه بقریة صغیرة، ویهم السائح الوقت الذي یلزمه للوصول إلى الجهة السیاحیة التي یرغب الذهاب إلیها، ویذهب بعض خب ا رء السیاحة إلى أن إمكانیة الوصول للموقع السیاحي تلعب دو ا رً مهماً لا یكاد یختلف عن الخصائص الجمالیة للموقع نفسه Abstract Transport is one of the important reasons for the prosperity of tourism in any country, and by the ways and means of transport of all kinds are provided the requirements of tourism promotion activities in the place of destination, as well as be linked to the tourist attraction markets demand. This means that transportation is the main base for tourism and exponentially, and also expresses the degree of urbanization and civilization and an indication of the economic progress of the country. The booming tourism and recreation industry in the regions and different countries linked to the progress of the ways and means of transport, and can not be tourist sites that would be more attractive for tourists as long as did not have access, regardless of what you offer of facilities and services, and affect the rapid and convenient transportation to tourism and recreation the distance and time are linked and the speed of transport currently has made the world more like a small village, and the matter tourist time that he have access to the tourist that wants to go to, and goes some tourism experts to access the site tourism plays an important role hardly differs from the aesthetic characteristics of the site itself